E-commerce during the COVID-19 sindemy: an inovation strategy for economic growth in the brazilian trade sector (2020-2021) (Research, Society and Development, 2022)
Nowadays, living with the COVID-19 phenomenon has become part of the so-called “new reality”, in order to impact the most different aspects of people's daily lives. In this context, the research question is to demonstrate how E-Commerce may have boosted retail commerce during the process defined as “syndemic collapse”, caused by the COVID-19 pandemic, between 2020 and 2021? Thus, the objective is to understand some factors that signal the contributions of e-commerce to the growth trend of the sector, through the analysis of the behavior of electronic commerce, in its dynamics and challenges faced, from the Schumpeterian perspective of the functioning of the economy, during the syndemic period from 2020 to 2021. The research has an exploratory nature in order to understand the phenomena studied. In this way, the results demonstrate that the syndemic brought a scenario of high uncertainty, which effectively caused unprecedented growth in the e-commerce sector even in a highly unstable context, managing not only to mitigate its recessive effects but also helped to maintain the growth trend of the sector. Even more, it was evidenced through the Schumpeterian theoretical foundation, that during this period, there was a “creative destruction” which provoked a “boom” of innovation in the sector and a rupture both quantitative and qualitative in consumer preferences giving rise to new behaviors by part of them.